2015
DOI: 10.1364/oe.23.00a829
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of the radiative transfer in a turbid medium using the synthetic iteration

Abstract: In this paper we propose the fast, but the accurate algorithm for numerical modeling of light fields in the turbid media slab. For the numerical solution of the radiative transfer equation (RTE) it is required its discretization based on the elimination of the solution anisotropic part and the replacement of the scattering integral by a finite sum. The solution regular part is determined numerically. A good choice of the method of the solution anisotropic part elimination determines the high convergence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
5
0
2
Order By: Relevance
“…In [29,30] the performance assessment of MDOM was conducted. In particular, the computational time of MDOM was measured for computing the angular distributions of the reflected radiances with different values of N and M. At the same time, it was found that for all N and M the computed radiances coincide in the entire range of angles except for the small glory region.…”
Section: Synthetic Iteration Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [29,30] the performance assessment of MDOM was conducted. In particular, the computational time of MDOM was measured for computing the angular distributions of the reflected radiances with different values of N and M. At the same time, it was found that for all N and M the computed radiances coincide in the entire range of angles except for the small glory region.…”
Section: Synthetic Iteration Methodsmentioning
confidence: 99%
“…A numerical comparison of the reflected radiance after the first iteration of MDOM is given in [29,30]. To calculate the glory region in the MDOM program, N = 801 and M = 256 are required, which corresponds to a sampling step of less than 0.5 • .…”
Section: )mentioning
confidence: 99%
“…Keeping in mind the advantages and limitations of the exact discrete ordinate approach and approximate solution techniques, we can formulate a hybrid approach based on synthetic iterations [29][30]. Originally such an approach was formulated in nuclear physics.…”
Section: Synthetic Iterationsmentioning
confidence: 99%
“…It excludes redundant information from the initial dataset and improves the efficiency of machine learning. This topic has been addressed frequently in the context of high-performance radiative transfer modelling (Natraj et al 2005;Liu et al 2006;Matricardi 2010;Efremenko et al 2014b;Budak et al 2015).…”
Section: Dimensionality Reductionmentioning
confidence: 99%